Phosphate adsorption kinetics and equilibria on natural iron and manganese oxide composites. (1st December 2022) - Chen, Ping; Zhou, Yuefei; Xie, Qiaoqin; Chen, Tianhu; Liu, Haibo; Xue, Sichuang; Zou, Xuehua; Wei, Lin; Xu, Liang; Zhang, Xin; Rosso, Kevin M.
Abstract: Although it is well known that phosphate retention in soils and sediments is strongly influenced by binding to secondary iron oxides, there have been relatively few studies examining its adsorption/desorption behavior on multicomponent particles of realistic natural complexity. In this study, natural Mn-rich limonite (LM), was used to prepare naturally complex Fe- and Mn-oxide composite materials to examine phosphate adsorption/desorption. To clarify the role of the Mn-oxides, results for the LM sample were compared to those for an acid treated version (LAT), in which the acid-extractable Mn-oxide fraction has been selectively eliminated while leaving the Fe-oxide fraction intact. The saturated adsorption capacity on LAT was almost double that on LM, suggesting that phosphate adsorption to the iron oxides is strongly occluded by the Mn-oxide fraction. This result is reinforced by the comparing the pH dependence and fits to adsorption isotherms, and by desorption experiments and STEM-EDS mapping showing that phosphate loading on Mn-oxides was limited. Hence, although the collective results confirm that phosphate uptake and strong binding is selectively controlled by the Fe-oxide fraction, our study reveals that the Mn-oxide fraction strongly interferes with this process. Therefore, phosphate uptake behavior on metal oxides cannot be predicted solely on the basis of the Fe-oxide fraction present, but instead must take into account the deleterious impacts of other intimately associated phases. For co-diagenetic Fe/Mn-oxide composites in particular, Mn-oxides appear to severely limit phosphate uptake on the Fe-oxide fraction, either by hindering access to binding sites on the Fe-oxide or by lowering their affinity for P. Graphical abstract: Natural Mn-rich limonite, denoted "LM", and those for an acid treated version, denoted "LAT", were used to prepare naturally complex Fe- and Mn-oxide composite materials to examine phosphate adsorption/desorption process. The saturated adsorption capacity on LAT was almost double that on LM, but the rate of achieving saturation on LM was higher than on LAT. Resulting thermodynamic quantities implied that adsorption is exergonic but driven by entropy that outweighs an underlying endothermic process, and that the net driving force decreases with increasing pH on LM but not on LAT. The collective results confirm that phosphate uptake and strong binding is selectively controlled by the Fe-oxide fraction. And another important conclusion is that the role of Mn-oxide fraction in the composite cannot be ignored because it clearly can severely limit the Fe-oxide uptake capacity. Image 1 Highlights: The saturated adsorption capacity on natural limonite was almost double after hydroxylamine hydrochloride treatment. Phosphate uptake and strong binding are selectively controlled by the Fe-oxide fraction in the natural Fe/Mn-oxide materials. The role of Mn-oxide fraction in the composite cannot be ignored because it can limit the Fe-oxide uptake capacity.